LIVED EXPERIENCES OF ELDERLY REMARRIED WIDOWS: ADJUSTMENT AND COPING TO NEW ROLES AS BI-PARENT - Abdullah Junior Serad Mangarun (Belitung Raya Foundation, Indonesia, 2020)
Background: At present, the existing studies which explore the factors influencing elderly widows to remarry and their achievement towards successful step-parenthood are limited. Remarriage and step-parenthood are integrated into the complexities of the social phenomena in human experiences, which entail coping and adjustments to life changes. Objective: The study explored the lived experiences of elderly widows regarding coping and adjustments to remarriage and step-parenting as new roles. Methods: The study made use of a phenomenological approach, particularly the transcendental approach, to have a better understanding of their lived-experience after remarriage. Self-made open-ended questions were raised in the series of interviews using interview guides. The study was conducted in Iligan City, Philippines, where all the six participants reside. Purposive sampling was used wherein participants are selected based on criteria necessary to answer the objectives of the study: (1) He/ she should be at least 60 years of age; (2) must be remarried after the death of the previous spouse; and, (3) must be a bi-parent. Thematic analysis was used for data analysis. Result: Three themes emerged in all interviews: (1) adjusting to a new marital role, (2) sharing responsible parenthood, and (3) rewarding new parental role. Results highlighted bi-parenting among elderly widows as an aptly complex lived- experience as widows enter remarriage. Conclusion: It is concluded that the remarried widows view life after remarriage with the new family and children as a positive experience despite the challenges. Remarriage and being with another family can improve the wellbeing of the elderly widows. Having children and a new partner around is an opportunity to bring back a complete family structure together. This research recommends further that the understanding of their experiences and phenomena should be the basis of identifying their status. Researchers and clinicians should provide essential information to elderly remarried widows about the healthy and proper coping and adjustment to this life-changing event.